The effect of Patient's Own Medication use on patient's self-reported medication knowledge during hospitalisation: a pre-post intervention study - Loes J. M. van Herpen-Meeuwissen; Bart J. F. van den Bemt; Hieronymus J. Derijks; Patricia M. L. A. van den Bemt; Barbara Maat; Hein A. W. van Onzenoort (BMC, 2022)
Abstract Background Improving patient's medication knowledge and consequently medication use is essential for optimal treatment outcomes. As patient knowledge about medication is currently suboptimal, interventions to optimise medication knowledge are necessary. Implementation of Patient's Own Medication (POM) in which patients bring their outpatient medication to the hospital, and nurses administer these during admission, may increase medication knowledge. The aim of this study is to explore the impact of POM use on self-reported medication knowledge of hospitalised patients compared to standard care. Patient's sense of medication safety, attitude to the provision of information, and to inpatient medication use were studied in both standard care and during POM use too. Method In this nationwide intervention study perceived medication knowledge was assessed with a questionnaire pre and post implementing POM use. The questionnaire assessed perceived medication knowledge at admission and discharge, medication safety during hospitalisation, the provision of information during hospitalisation and at discharge, and inpatient medication use during hospitalisation. Patients' answers were categorised into positive and negative/neutral. The proportion of patients with adequate medication knowledge, in the standard care and POM use group at hospital admission and discharge, were calculated and compared with adjustment for potential confounders. Results Among the 731 patients (393 received standard care and 338 POM) who completed the questionnaire (80.2%), POM use seemed to be positively associated with self-reported knowledge on how to use medication at discharge (adjusted OR: 3.22 [95% CI 2.01-5.16]). However, for the other two knowledge related statements POM use was not associated. Medication knowledge at admission was the most important variable associated with perceived medication knowledge at discharge. The majority perceived POM use to be safer (52.9% of standard care patients versus 74.0% POM users; P <  0.01), POM users knew better which medicines they still used during hospitalisation (85.8% versus 92.3% resp.; P = 0.01), and most patients preferred POM use regardless of having experienced it (68.2% versus 82.2% resp.; P <  0.01). Conclusion POM use positively affects patient's medication knowledge about how to use medication and patients' perception of medication safety. With POM use more patients have a positive attitude towards the provision of information. The majority of patients prefer POM use. In conclusion, POM use seems a valuable intervention and requires further investigation.